A comparative study of bilateral subthalamic nucleus DBS in Parkinson's disease in young versus old: A single institutional study. (December 2019) - Vats, Atul; Amit, Amit; Doshi, Paresh
Highlights: STN-DBS is a safe and effective treatment option for advanced Parkinson's disease. Elderly Parkinson's patients can be safely offered STN DBS with equal efficacy. DBS in elderly group improves the caretaker burden. Abstract: To compare outcome between young [<65 yrs] and old [>65 yrs] patients of Parkinson's disease who underwent bilateral STN DBS a non-randomized retrospective study was done. 20 young (Young group) and 20 elderly (Old group) patients with matched baseline UPDRS were selected and followed up for 2 years after deep brain stimulation (DBS) surgery. The total and motor UPDRS, before, one year and two years after surgery was compared. PDQ39 a quality of life questionnaire and MMSE were also recorded. Zarit care burden interview (ZCBI) was used to analyse caregiver burden. Analysis of data was done using Mann-Whitney Test as the data was ordinal. The difference was not statistically significant at 1st and 2nd year of follow up in total and motor UPDRS. A significant reduction in Levodopa equivalent daily dose was seen in young and old group from preoperative period to 1st & then 2nd year of follow up. The difference was not statistically significant (P = 0.946) at 1st (P = 0.946) and at 2nd year (P = 0.989). Both the groups showed improvement in their PDQ39. The difference was not statistically significant at 1st (P = 0.636) and at 2nd year of follow up (P = 0.417). Caregiver burden (ZCBI) improved in both the groups and the difference was not statistically significant at 1st (P = 0.105) and at 2nd year of follow up (P = 0.078).In this study STN DBS didn't lead to any cognitive decline (MMSE) whatever is the age of patient during follow up. Bilateral STN DBS for Parkinson's disease is equally effective in young and elderly patients.